MtDNA segregation in heteroplasmic tissues is common in vivo and modulated by haplotype differences and developmental stage - Burgstaller, Joerg Patrick; Johnston, Iain G; Jones, Nick S; Albrechtová, Jana; Kolbe, Thomas; Vogl, Claus; Futschik, Andreas; Mayrhofer, Corina; Klein, Dieter; Sabitzer, Sonja; Blattner, Mirjam; Gülly, Christian; et al. (Cell reports, 2014)
The dynamics by which mitochondrial DNA (mtDNA) evolves within organisms are still poorly understood, despite the fact that inheritance and proliferation of mutated mtDNA cause fatal and incurable diseases. When two mtDNA haplotypes are present in a cell, it is usually assumed that segregation (the proliferation of one haplotype over another) is negligible. We challenge this assumption by showing that segregation depends on the genetic distance between haplotypes. We provide evidence by creating four mouse models containing mtDNA haplotype pairs of varying diversity. We find tissue-specific segregation in all models over a wide range of tissues. Key findings are segregation in postmitotic tissues (important for disease models) and segregation covering all developmental stages from prenatal to old age. We identify four dynamic regimes of mtDNA segregation. Our findings suggest potential complications for therapies in human populations: we propose "haplotype matching" as an approach to avoid these issues.
Keywords: Disease Models, Animal; Humans; modely genetické; Mice; Animals; Molecular Sequence Data; Haplotypes; mitochondriální DNA; haplotypy; myši; Amino Acid Sequence; DNA, Mitochondrial; sekvence aminokyselin; zvířata; molekulární sekvence - údaje; modely nemocí na zvířatech; Models, Genetic; lidé